2000
DOI: 10.1023/a:1005460509677
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The association of hepatolithiasis (HL) and peripheral cholangiocarcinoma (PCC) has been well recognized. However, information concerning the impact of hepatolithiasis on patients with peripheral cholangiocarcinoma is sparse and therefore difficult to assess. A total of 162 consecutive patients with histologically proven peripheral cholangiocarcinoma were treated surgically at Chang-Gung Memorial Hospital between 1977 and 1994. Among them, 106 patients (65.4%) had associated hepatolithiasis (PCC + HL group), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to the previous studies, the incidence of postoperative complications was 12.0-38.5% after LR, 24.3-38.0% after HE and 2.1-40.0% after IHDE. 5 7 8 10 18 19 20 21 22 23 In this study, the incidence of postoperative complications was 29.9% after LR, 12.0% after IHDE and there were no cases of postoperative complications after HE. The incidence of complications in patients who underwent LR and IHDE was in concordance with the results of prior studies, but the patients who underwent HE showed a highly lower incidence of complications.…”
Section: Discussionmentioning
confidence: 48%
“…According to the previous studies, the incidence of postoperative complications was 12.0-38.5% after LR, 24.3-38.0% after HE and 2.1-40.0% after IHDE. 5 7 8 10 18 19 20 21 22 23 In this study, the incidence of postoperative complications was 29.9% after LR, 12.0% after IHDE and there were no cases of postoperative complications after HE. The incidence of complications in patients who underwent LR and IHDE was in concordance with the results of prior studies, but the patients who underwent HE showed a highly lower incidence of complications.…”
Section: Discussionmentioning
confidence: 48%
“…There was a report indicating that the prevalence of hepatolithiasis in the patients with ICC was up to 65.4%, which obviously confirmed the development from hepatolithiasis and chronic inflammation to carcinoma. [21] But the relationship between hepatolithiasis, choledocholithiasis, and the sarcomatoid changes of ICC, and finally SIC, remains a mystery. More clinical and genetic research is required.…”
Section: Discussionmentioning
confidence: 99%